Health promotion as a preventive effort against non-communicable diseases in adolescents - Waliyanti, Ema; Susanti, Afrinia Nanda; Faiqoturrohmah, Faiqoturrohmah; Wahdah, Indri Zahrotul; Anugerah, Shelany (Community Empowerment, 2025)
Adolescents are an age group that is increasingly vulnerable to non-communicable diseases (NCDs) such as hypertension and diabetes. This is triggered by unhealthy lifestyles and low health literacy. This community service activity aims to increase students’ knowledge and awareness of the importance of a healthy lifestyle as a preventive measure against NCDs. The intervention was carried out at SMK Muhammadiyah Bangunjiwo and involved 40 grade X students. The series of activities included a pre-test and post-test carried out using Quizizz, as well as a health education session with four main topics: physical health, nutrition, mental health and reproductive health. The results of the paired sample t-test showed a significant increase in the average student score from 72.6 (pre-test) to 88.5 (post-test) (p = 0.000). This increase shows that an interactive and contextual educational approach can improve students’ understanding of a healthy lifestyle. This program emphasizes the importance of school-based health education as a preventive strategy to reduce the risk of NCDs early.